2022
DOI: 10.1093/ofid/ofac397
|View full text |Cite
|
Sign up to set email alerts
|

Long COVID Symptomatology After 12 Months and Its Impact on Quality of Life According to Initial Coronavirus Disease 2019 Disease Severity

Abstract: Introduction Long COVID is characterized by a variety of symptoms and an important burden for affected people. Our objective was to describe Long COVID symptomatology according to initial COVID-19 severity. Methods Predi-COVID cohort study participants, recruited at the time of acute COVID-19 infection, completed a detailed 12-month symptoms and quality of life questionnaire. Frequencies and co-occurrences of symptoms were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 44 publications
1
60
0
Order By: Relevance
“…Importantly, at the time of writing only one report by Wang et al [45], indicated the possibility of increased rotavirus A-mediated enteric infections in COVID-19 patients. These findings are intriguing given the propensity for COVID-19 patients to suffer from enteric symptoms [3], including nausea [46] and diarrhoea [47]. Whether the rotavirus, especially in adults, is associated with COVID-19 gastrointestinal symptoms, or the enteric effects exacerbate the expression of rotavirus C-associated genes is still unknown and will have to be investigated in dedicated follow-up studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, at the time of writing only one report by Wang et al [45], indicated the possibility of increased rotavirus A-mediated enteric infections in COVID-19 patients. These findings are intriguing given the propensity for COVID-19 patients to suffer from enteric symptoms [3], including nausea [46] and diarrhoea [47]. Whether the rotavirus, especially in adults, is associated with COVID-19 gastrointestinal symptoms, or the enteric effects exacerbate the expression of rotavirus C-associated genes is still unknown and will have to be investigated in dedicated follow-up studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although COVID-19 is primarily considered a respiratory disease, it clinically often presents with general (fever, myalgia and/or fatigue) and respiratory symptoms (cough and/or dyspnea). Moreover, an emergence of new variants has led to the more frequent presentation of gastrointestinal symptoms (appetite loss, nausea, vomiting and diarrhoea) [3], indicating a potential involvement of the gastrointestinal tract in COVID-19. More specifically, SARS-CoV-2 has been shown to be able to infect and replicate in enterocytes in vitro [4].…”
Section: Introductionmentioning
confidence: 99%
“…Persisting symptoms were collected using a list of 62 symptoms [11], further divided into 8 categories: ear/nose/throat symptoms, neurological and ocular symptoms, general symptoms, cardio-respiratory symptoms or diseases, gastrointestinal symptoms, vascular and ganglionic symptoms or diseases, urinary symptoms, and skin symptoms (see Online Supplementary Table 1 for the full list).…”
Section: Study Populationmentioning
confidence: 99%
“…A one-size-fits-all care strategy for people with Long COVID is therefore not possible and a better understanding of sub-forms of Long COVID would allow to develop personalized care for people with Long COVID or be integrated as a screening tool for future clinical trials [11]. To date, few studies used clustering analysis to identify and characterize different Long COVID phenotypes [8,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Statistics shows that among these symptoms, the symptoms of nervous system and cardiovascular system are the most, and seriously affect the quality of life of patients. [ 4 ] At present, there is no specific drug to treat “long COVID-19.” [ 4 , 5 ] The treatment of “long COVID-19” in modern medicine mainly use of drugs to improve related symptoms, combined with multi-disciplinary rehabilitation model and telerehabilitation. Research shows that traditional Chinese medicine combined with moxibustion has a good effect on improving the symptoms of patients with chronic coronavirus disease.…”
Section: Introductionmentioning
confidence: 99%